Demonstration of asynchronous computational ghost imaging through strong scattering media. (October 2022) - Wan, Wenxiu; Luo, Chunling; Guo, Fumin; Zhou, Jian; Wang, Peilin; Huang, Xiaoyan
Highlights: The asynchronous detection way has been introduced into the computational ghost imaging to well eliminate the requirement of detection system in the aspects of time and intensity in the spatial domain. In this paper, we have introduced a kind of algorithm based on compressed sensing into the asynchronous computational ghost imaging (ACGI) system, where sharp ghost images can be reconstructed with much fewer measurements. We have experimentally investigated the robustness of the ACGI system through strongly scattering media and the ghost image can still be reconstructed by means of the asynchronous detection, which will be very helpful for the real application of the ghost imaging in the hostile environment. Our work offers a new way to realize ghost imaging in the asynchronous detection way, where the requirement of the synchronous detection in the time and intensity aspects can well eliminated, which may be very useful for real applications of ghost imaging in X-ray or weak light environments. The instrument costs and the amount of sampling data are greatly declined in our ACGI proposal with the asynchronous detection. Abstract: Imaging through strong scattering media is still one of the difficult challenges in the optical imaging field since the intensity information of target objects can be severely destroyed and heavily reduced by scatterers. The ghost imaging technique only using a single-pixel detector offers compelling advantages for detecting such weak signals. Here we propose a novel kind of imaging proposal, named asynchronous computational ghost imaging (ACGI), which is capable of capturing the ghost image of an unknown object by using the asynchronous detection. The theoretical explanation and experimental examples are given to show the influence of parameters of the asynchronous detection on the image quality of the ACGI system. To improve the image quality, we introduce a kind of algorithm based on compressed sensing into the ACGI system, where sharp ghost images can be reconstructed with much fewer measurements. More importantly, we experimentally investigate the robustness of the ACGI system through strong scattering media and the ghost image can still be reconstructed by means of the asynchronous detection. Our work offers a new way to realize ghost imaging through strong scattering media in the asynchronous detection way, where the requirement of the synchronous detection in the time and intensity aspects can be largely reduced, which may be very useful for real applications of ghost imaging in X-ray or weak light environments.